Effects of Mind Mapping and Guided Peer Feedback on Eighth Graders’ Descriptive Writing - Monica Rahmawanda; Patuan Raja; Flora (LPPM Universitas Advent Indonesia, 2026)
This study examined the use of mind mapping and guided peer feedback in teaching descriptive writing to eighth-grade EFL students. The study was conducted in Class VIII-5 of SMP Negeri 22 Bandar Lampung, involving 30 students selected through purposive sampling. A quantitative one-group pre-test and post-test design was used due to the limited number of available classes at the research site, which made it impractical to form a separate control group. The students were asked to write descriptive texts, and their writings were scored by two raters using an analytic scoring rubric adapted from Jacobs et al. (1981). The rubric covered five aspects of writing: content, organization, vocabulary, language use, and mechanics. The data were analyzed through descriptive statistics, inter-rater reliability analysis, normality testing, a paired-samples t-test, N-gain analysis, and Cohen’s d for effect size. The results indicate a significant improvement in students’ descriptive writing achievement after the implementation of mind mapping and guided peer feedback, t(29) = 29.872, p < .001, with a very large effect size (Cohen’s d = 5.45). Among the five writing aspects, mechanics showed the highest proportional improvement, followed by vocabulary, content, organization, and language use. These findings indicate that the two techniques supported different stages of the writing process. Mind mapping helped students prepare ideas before drafting, while guided peer feedback helped them review and revise their drafts using clearer writing criteria. For teachers, these findings suggest that combining visual planning tools with structured peer review within a single writing sequence can meaningfully enhance students’ writing performance, particularly in writing conventions and content development. Therefore, the integration of mind mapping and guided peer feedback can be considered a useful strategy for supporting descriptive writing instruction in junior high school EFL classrooms.